2013
DOI: 10.1002/maco.201307078
|View full text |Cite
|
Sign up to set email alerts
|

Qualitative analysis of Zircaloy‐4 cladding air degradation in O2–N2 mixtures at high temperature

Abstract: This article is devoted to the qualitative analysis of the Zircaloy‐4 degradation mechanism at 850 °C in oxygen/nitrogen partial pressure atmospheres. Thermogravimetry, optical microscopy, scanning electron microscopy, and energy dispersive X‐ray spectrometry, are used to provide some information regarding the oxidation kinetics and the various phases involved along the process. The kinetic curves reveal two stages: a pre‐transition and a post‐transition one. Oxide growth during the pre‐transition stage is con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 21 publications
4
21
0
Order By: Relevance
“…In order to understand oxidation during loss of coolant accidents (LOCA) many authors have researched oxidation of zirconium alloys in the 600-1200°C temperature range [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to understand oxidation during loss of coolant accidents (LOCA) many authors have researched oxidation of zirconium alloys in the 600-1200°C temperature range [21][22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Whether oxidation occurs in air or steam zirconium alloys typically demonstrate a transition to accelerated breakaway corrosion kinetics [21][22][23]. Research has indicated this acceleration is associated with the formation of large cracks perpendicular to the metal-oxide interface, and the formation of a defective, heavily-fractured oxide layer [21,24,25].…”
Section: Introductionmentioning
confidence: 99%
“…This nonhomogeneity could be caused by different thermal-hydraulic boundary conditions at the external and internal surfaces of the tube segments, by changing gas composition along the sample due to consumption of oxygen, and by the inherent local initiation of nitrogen attack as described e.g. in [12,15]. Although the experiments did not exhibit ideal parabolic to linear transitions, the rate constants of all tests were determined based on parabolic and linear reaction kinetics, i.e.…”
Section: Analysis and Discussion Of Experimental Resultsmentioning
confidence: 99%
“…Most samples reveal a non-homogeneous surface. This is caused by the local initiation of nitrogen attack as it was observed in earlier experiments on air oxidation of zirconium alloys [12,15]. Furthermore, and especially for gas mixtures with low concentration of one gas and increasing with temperature, the composition and therefore the oxidation conditions may change with the height of the sample.…”
Section: Post-test Appearance and Metallographymentioning
confidence: 85%
See 1 more Smart Citation